Study on the Mechanism of Qing-Fei-Shen-Shi Decoction on Asthma Based on Integrated 16S rRNA Sequencing and Untargeted Metabolomics. (15th February 2023) - Hu, Haibo; Zhao, Guojing; Wang, Kun; Han, Ping; Ye, Haiyan; Wang, Fengchan; Liu, Na; Zhou, Peixia; Lu, Xuechao; Zhou, Zhaoshan; Cui, Huantian
Abstract : Qing-Fei-Shen-Shi decoction (QFSS) consists of Prunus armeniaca L., Gypsum Fibrosum, Smilax glabra Roxb., Coix lacryma-jobi L., Benincasa hispida (Thunb.) Cogn., Plantago asiatica L., Pyrrosia lingua (Thunb.) Farw., Houttuynia cordata Thunb., Fritillaria thunbergii Miq., Cicadae Periostracum, and Glycyrrhizae Radix Et Rhizoma Praeparata Cum Melle . QFSS shows significant clinical efficacy in the treatment of asthma. However, the specific mechanism of QFSS on asthma remains unclear. Recently, multiomics techniques are widely used in elucidating the mechanisms of Chinese herbal formulas. The use of multiomics techniques can better illuminate the multicomponents and multitargets of Chinese herbal formulas. In this study, ovalbumin (OVA) was first employed to induce an asthmatic mouse model, followed by a gavage of QFSS. First, we evaluated the therapeutic effects of QFSS on the asthmatic model mice. Second, we investigated the mechanism of QFSS in treating asthma by using an integrated 16S rRNA sequencing technology and untargeted metabolomics. Our results showed that QFSS treatment ameliorated asthma in mice. In addition, QFSS treatment affected the relative abundances of gut microbiota including Lactobacillus, Dubosiella, Lachnospiraceae_NK4A136_group, and Helicobacter . Untargeted metabolomics results showed that QFSS treatment regulated the metabolites such as 2-(acetylamino)-3-[4-(acetylamino) phenyl] acrylic acid, D-raffinose, LysoPC (15 : 1), methyl 10-undecenoate, PE (18 : 1/20 : 4), and D-glucose6-phosphate. These metabolites are associated with arginine and proline metabolism, arginine biosynthesis, pyrimidine metabolism, and glycerophospholipid metabolism. Correlation analysis indicated that arginine and proline metabolism and pyrimidine metabolism metabolic pathways were identified as the common metabolic pathways of 16s rRNA sequencing and untargeted metabolomics. In conclusion, our results showed that QFSS could ameliorate asthma in mice. The possible mechanism of QFSS on asthma may be associated with regulating the gut microbiota and arginine and proline metabolism and pyrimidine metabolism. Our study may be useful for researchers to study the integrative mechanisms of Chinese herbal formulas based on modulating gut microbiota and metabolism.